Interactive modeling of complex geometric details based on empirical mode decomposition for multi-scale 3D shapes. (June 2017) - Zhang, Dongbo; Wang, Xiaochao; Hu, Jianping; Qin, Hong
Highlights: We propose an interactive modeling system for geometric details for multi-scale 3D shapes. Our system can transfer different scale details individually or in a concerted way. Our system is conducted in real-time and keeps the overall shape of target surface. Our system can facilitate many applications, including detail enrichment, model recreation, and shape completion. Abstract: In this paper we develop an interactive modeling system for complex geometric details transformation based on empirical mode decomposition (EMD) on multi-scale 3D shapes. Given two models, we aim to transfer geometric details from one model to another one in an interactive manner. Taking full advantages of the multi-scale representation computed via EMD, different-scale geometric details can be transferred individually or in a concerted way, which makes our algorithm much more flexible than cut-and-paste and cloning based methods in transferring geometry details. In this process, the target surface with new transferred details could be generated by a mesh reconstruction method widely used in Laplacian surface editing. With the original positions of target surface serving as the soft constraints, the overall shape of the target model will be fully preserved. Our method can also support real-time continuous details transfer. Compared with state-of-the-art algorithms, our method provides an easier-to-use modeling tool and produces varied modeling results. We demonstrate the effectiveness of our modeling tool with various applications, such as detail transfer and enrichment, model reuse and recreation, and detail recovery for shape completion.